Internationalisation of Chinese firms in Africa: An Exploratory Study - Habib Jandira, Murtaza Amin (2014)
Chinese internationalisation in Africa has generally been viewed with an air of negativity. Voices of economic colonisation have been commonly raised. However, the trend is now changing as Chinese firms are altering their strategy, with a push towards community development and improving reputation. Africa is now China‟s largest trade partner and Chinese firms are realising the benefits of a mineral rich Africa. In light of this, the aim of this management project is to analyse the internationalisation strategies of Chinese firms in Africa, by reviewing the drivers of internationalisation, studying their preferred entry strategies and assessing the benefits accruing to Africa and the Chinese firms. This project aims to provide crucial insight for potential investors in Africa as they try to replicate the success of Chinese firms. To achieve these objectives, an exploratory study of nine firms was completed, with a focus on the natural resource industry. The firms that were chosen were operating across different countries within Africa. Data was collected from a triangulation of various secondary sources, ranging from journal articles, newspapers, corporate websites and magazines. A content analysis was used to analyse the collated data to reveal any patters. Results indicated that the primary driver of Chinese internationalisation remains access to natural resources. Foreign direct investment remains the preferred entry strategy, primarily due to the managerial control it offers. Chinese firms create jobs in Africa, transfer skills and spend vast amounts of money in the local economies. In return, they enjoy exclusive access to natural resources and access to cheap factors of production. Companies also are trying to improve the reputation of China, by engaging in community, infrastructure and industry development and in return are improving geo-political relationships with African leaders. Lastly, the implications for investors is that they have to realise that Chinese firms first possess the necessary finance and technical expertise, are not averse to developing infrastructure and are willing to operate in risky environments.